2013
DOI: 10.1123/jsr.22.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Low-Level Laser Therapy Combined With an Exercise Program to Reduce Pain and Increase Function in Adults With Shoulder Pain: A Critically Appraised Topic

Abstract: Shoulder pain is a common musculoskeletal condition that affects up to 25% of the general population. 1 Shoulder pain can be caused by any number of underlying conditions including subacromial impingement syndrome, rotator-cuff tendinitis, and biceps tendinitis. 2,3 Regardless of the specific pathology, pain is generally the number 1 symptom associated with shoulder injuries and can severely affect daily activities 4 and quality of life 5,6 of patients with these conditions. Two of the primary goals in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
(21 reference statements)
0
15
0
2
Order By: Relevance
“…This study was designed to determine the effect of flexibility training from static to dynamic stretching, from active warming to passive heating. Then one of the other goals is to increase ROM (Range of Motion) [30]. From the above results after conducting research from starting to pretest, the results showed that all samples were still in the low category, then carried out treatment for 16 meetings with the provision of flexibility training in order to determine the effect on the results of the dollyo chagi kicks, until the last step was done posttest and get the result is that the sample has improved mastery of the Dollyo Chagi kick technique.…”
Section: Resultsmentioning
confidence: 99%
“…This study was designed to determine the effect of flexibility training from static to dynamic stretching, from active warming to passive heating. Then one of the other goals is to increase ROM (Range of Motion) [30]. From the above results after conducting research from starting to pretest, the results showed that all samples were still in the low category, then carried out treatment for 16 meetings with the provision of flexibility training in order to determine the effect on the results of the dollyo chagi kicks, until the last step was done posttest and get the result is that the sample has improved mastery of the Dollyo Chagi kick technique.…”
Section: Resultsmentioning
confidence: 99%
“…Весьма популярная в нашей стране лазеротерапия может быть полезным дополнением медикаментозного лечения РПОМТ. Так, лазеротерапия в комбинации с упражнениями повышает эффективность терапии боли в плече, хотя самостоятельная ценность лазеротерапии остается неясной [68]. Клинические исследования подтверждают умеренное обезболивающее действие лазеротерапии при латеральном эпикондилите [69,70].…”
Section: немедикаментозные методы лечения рпомтunclassified
“…In jüngeren Übersichtsarbeiten wird die Anwendung bei Sehnenverletzungen als nicht eindeutig bewertet [4]. In der Behandlung muskulärer Schmerzen sowie verletzungsassoziierter Folgen ist die Zahl wegweisender und positiver Studien quantitativ zwar größer, in der qualitativen Bewertung wird jedoch auch hier deutlich, dass weitere Studien nötig sind, um eine abschließenden Aussage treffen zu können [20,23].…”
Section: Muskuläre Verletzungen Im Sportunclassified